(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Mathematical modelling of population dynamics is an essential approach for understanding how populations of organisms change over time in response to various biological, environmental, and ecological factors. These models utilize mathematical equations and techniques to describe the growth, decline, and stability of populations, as well as the interactions between individuals within a population and between species in an ecosystem. The primary goal of such models is to predict future population trends and to identify the underlying processes that drive these changes. The simplest population growth models, such as exponential and logistic growth, offer foundational insights into how populations grow under idealized conditions and environmental limitations. More advanced models, such as age-structured models, consider the effects of age-specific birth and death rates, while stochastic models incorporate randomness and uncertainty into population predictions. Furthermore, models that account for spatial distribution, migration, and interspecies interactions, such as predator-prey dynamics and competition, provide a more nuanced understanding of population behavior in complex environments.